2015
DOI: 10.2110/palo.2013.124
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Paleoecology of Miocene Coral-Associated Mollusks From East Kalimantan (Indonesia)

Abstract: This study is a preliminary assessment of an extremely diverse Tortonian (late Miocene) mollusk assemblage from a coral carpet environment preserved at Bontang (East Kalimantan, Indonesia). Even though coral-associated aragonitic faunas are rarely well preserved, the composition of the assemblage described here can be used to address the following questions: (1) How do the mollusk assemblages in coral habitats differ from other habitats, and (2) What is the effect of sampling on estimates of taxon richness? Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…So for taxonomic use, the collections might be adequate to develop taxonomic frameworks, but they are not suitable on their own for studies of diversity or ecology. For this work, additional ecologically sampled collections are required (Bromfield and Pandolfi 2011;Novak et al 2013;Kusworo et al 2015;Santodomingo et al 2015).…”
Section: Samplingmentioning
confidence: 99%
“…So for taxonomic use, the collections might be adequate to develop taxonomic frameworks, but they are not suitable on their own for studies of diversity or ecology. For this work, additional ecologically sampled collections are required (Bromfield and Pandolfi 2011;Novak et al 2013;Kusworo et al 2015;Santodomingo et al 2015).…”
Section: Samplingmentioning
confidence: 99%
“…These habitats were dominated by branching colonies of the genera Dictyaraea , Seriatopora , Alveopora , Goniopora and Porites , and were the main habitat of Acropora species within the aspera group. Coral carpets usually co‐occur with seagrass environments (Kusworo et al ., ), and are interpreted as developing in shallow lagoonal palaeonvironments. Thus, it seems that species in the aspera group occupied a similar environment to one of those currently occupied (Wallace, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other coral species of this locality include Antillia constricta , Pavona decussata , Porites nigrescens and Goniopora planulata (Gerth, ). Similar mixed mollusc–coral faunas of Miocene age in East Kalimantan have been interpreted as coral carpets that developed in sheltered habitats (Kusworo et al ., ). This suggests that A. grandis occupied a similar habitat in the Miocene as it does on modern reefs.…”
Section: Systematic Accountmentioning
confidence: 97%
See 1 more Smart Citation
“…Those sediments are covered by nonfossiliferous clay and fine sandstone beds likely representing the lowest deposits of a fluvial series. The locality is described in detail by Kusworo et al (2015). The shells used in this study were collected from patches of branching corals found on a bedding plane of marine silty clay (hand-collected sample SR45) and a bulk sample taken from the same bed (sample SR50).…”
Section: Introductionmentioning
confidence: 99%